2023
DOI: 10.3390/pr11092721
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS and GC-MS Identification of Metabolites from the Selected Herbs and Spices, Their Antioxidant, Anti-Diabetic Potential, and Chemometric Analysis

Hafiza Sehrish Kiani,
Baber Ali,
Mohammad Khalid Al-Sadoon
et al.

Abstract: Culinary herbs and spices are widely used in daily diets. Pakistan’s flora is enriched with phytochemicals due to a diverse range of land. Phytochemicals, including volatile and non-volatile compounds, have captured much interest due to their numerous health advantages and significance in daily diet. The present study aimed to conduct in-depth metabolomic profiling of Pakistani-grown fenugreek leaves (Trigonella foenum-graecum), fennel seeds (Foeniculum vulgare), mint leaves (Mentha royleana), coriander seeds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 100 publications
(136 reference statements)
2
7
0
Order By: Relevance
“…Overall, TPC and TFC are highly correlated with antioxidant activities (DPPH and FICA). The results are supported by previous studies where it has been reported that total phenolics and flavonoids are the main compounds responsible for the antioxidant capacity of fruits, vegetables, and herbs [ 25 , 43 , 44 ]. Moreover, a biplot analysis ( Figure 1 ) was conducted to further understand the contribution of selected sour fruits in phenolic contents and their antioxidant activities.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, TPC and TFC are highly correlated with antioxidant activities (DPPH and FICA). The results are supported by previous studies where it has been reported that total phenolics and flavonoids are the main compounds responsible for the antioxidant capacity of fruits, vegetables, and herbs [ 25 , 43 , 44 ]. Moreover, a biplot analysis ( Figure 1 ) was conducted to further understand the contribution of selected sour fruits in phenolic contents and their antioxidant activities.…”
Section: Resultssupporting
confidence: 89%
“…The distinct qualities and advantageous potential of phenolic compounds, such as their anti-inflammatory, antioxidant, antidiabetic, antimicrobial, and anticarcinogenic qualities, have drawn the attention of scientists [ 25 ]. Table 1 displays black lemons’, unripe mangoes’, and unripe grapes’ phenolic content and antioxidant examinations.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most prevalent secondary metabolites of the Lamiaceae plant family, this compound offers a multitude of health benefits, mainly related to its high antioxidant potential as well as its antiseptic and anticancer properties. Its efficacy as an anti‐inflammatory, neuroprotective, and hepatoprotective agent has been confirmed (Hitl et al., 2021 ; Kiani et al., 2023 ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, herbs and spices have been used in foods for millennia for flavor enhancement and quality preservation (Kiani et al., 2023 ). Adding plant matter to yogurt therefore appears to be an effective way of providing natural phytochemicals, which represents a new trend for improving the nutritional characteristics and product functionalities.…”
Section: Intoductionmentioning
confidence: 99%
“…A higher concentration of OH groups in a flavonoid has previously been shown to be advantageous for biological activities [24]. The structural arrangement of each ring, a catechol group in the B ring, its number of hydroxyl groups, and many double bonds in the C ring further affect each ring's ability to act as an antioxidant in extracts.…”
Section: Pearson Correlation Analysis Between Phenolic Contents and T...mentioning
confidence: 99%